Immersive Technologies in 5G-Enabled Networks: A Systematic Review of Publication Trends and Adoption Recommendations - Nkosikhona Theoren Msweli; Alfred Thaga Kgopa (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
Fifth-generation (5G) infrastructure is unlocking the transformative potential of immersive technologies across various sectors. This research explores the nexus between immersive technologies and 5G network deployments, based on trends in publications, factors in adoption, as well as policy aspects. Adopting a systematic approach, peer-reviewed publications were analyzed, considering only publications from the previous 10 years, i.e., 2015-2025. The PRISMA approach was used to identify research articles that resulted in 43 studies selected for the review. The analysis of reviewed literature shows a surge in publications after 2018, with healthcare, academia, and sectoral training being the predominant fields of application. The synthesis of existing studies further reveals that infrastructural barriers are the most frequently reported constraint to adoption, followed by technical limitations and device readiness challenges. These constraints are severe and endured in developing countries. The reviewed literature identifies approaches for the telecommunications industry and policymakers, such as selective 5G deployments across different organisations to enable experimentation. Notwithstanding 5G technological advancements, it is unclear how organisations would adapt to such advancements, a gap that makes it challenging to assess its wider sectoral contributions. There is minimal research focusing on 5G adoption barriers, a gap that points to a need for future research adopting different methodological approaches, to investigate opportunities alongside risks. This research contributes to the analysis by tracking trends and barriers, along with providing actionable avenues for scaling immersive applications in constrained-resource settings.